The Political Economy of Household Expenditure in Indonesia - Alexandi, Muhammad Findi; Murti, Prima Puspita Indra (Faculty of Sharia and Law, UIN Syarif Hidayatullah Jakarta, 2022)
The study analyzed the data released by BPS RI from 2010 to 2019. There is a tendency for the growth rate of Indonesian people's spending on food and non-food to be lower than the growth rate of its national disposable income. This shows that Indonesian income has entered the upper-middle-income level. Further, some of the income earned has been saved or invested. A descriptive analysis and double linear regression analysis are used in this study. Data shows that household spending on GDP in Indonesia is more than 50%. This study finds a shift in household expenditure structure between food and non-food consumption. Food expenditure experienced a steep decline from 1999 to 2019. The analysis shows that independent variables encompassing inflation, national disposable income, public saving position and ZIS funds distribution significantly influenced household expenditure. AbstrakPenelitian ini menganalisis data yang dirilis BPS RI tahun 2010 hingga 2019 tentang kecenderungan laju pertumbuhan pengeluaran masyarakat Indonesia untuk makanan dan nonmakanan. Data menjelaskan bahwa pengeluaran makana lebih rendah dari pendapatan disposabel nasional. Hal ini menunjukkan bahwa pendapatan masyarakat Indonesia memasuki tingkat pendapatan menengah ke atas. Saat ini, lebih banyak orang yang menginvestasikan pendapatan mereka. Penelitian ini menggunakan analisis deskriptif dan analisis regresi linier berganda dan menunjukkan bahwa pengeluaran rumah tangga terhadap PDB di Indonesia lebih dari 50%. Struktur pengeluaran rumah tangga dari konsumsi makanan bergeser ke bukan makanan. Ditemukan bahwa pengeluaran pangan mengalami penurunan tajam dari tahun 1999 hingga 2019. Hasil analisis menunjukkan bahwa variabel bebas yang meliputi inflasi, pendapatan disposabel nasional, posisi tabungan masyarakat, dan penyaluran dana ZIS berpengaruh signifikan terhadap pengeluaran rumah tangga.